Blastocyst development rate influences singleton gestational age of similarly graded blastocysts after vitrified–warmed single embryo transfer cycles. Issue 3 (March 2022) - Zhu, Lihua; Wang, Jie; Chen, Linjun; Jiang, Weihua; Fang, Junshun; Wang, Shanshan; Lin, Fei; Zhang, Ningyuan
Abstract: Research question: Does the development rate of blastocysts influence neonatal outcomes after blastocyst transfer cycles when the morphological score of the transferred blastocysts is similar? Design: A retrospective study involving singleton live births born to 1280 women undergoing single frozen blastocyst transfers (FBTs) between January 2016 and December 2018 at a tertiary care centre. Patients were grouped into day-5 or day-6 groups depending on the development rate of blastocysts. These were further grouped into four groups based on the blastocyst inner cell mass and trophectoderm scoring: excellent (AA); good (AB or BA); average (AC, CA or BB); and poor (BC or CB). The primary outcomes were gestational age and singleton birth weight. Results: Singletons resulting from day-5 single FBT were at a lower risk of preterm birth than those resulting from day-6 single FBT (adjusted OR 0.63, 95% CI 0.41 to 0.97, P  = 0.035). In the day-5 good-quality blastocyst group and day-5 average-quality blastocyst group, singletons were at a lower risk of preterm birth than those resulting from day-6 groups, respectively (adjusted OR 0.22, 95% CI 0.08 to 0.63, P  = 0.005 and adjusted OR 0.52, 95% CI 0.29 to 0.94, P  = 0.03). Conclusions: Day-6 single FBT was associated with a higher risk of preterm birth compared with day-5 single FBT in good and average morphological scoring blastocysts. Our analysis was restricted to women with singleton births from single FBTs. Future prospective studies are required to confirm the findings.